2017
DOI: 10.4049/jimmunol.1602142
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Selective Oral ROCK2 Inhibitor Reduces Clinical Scores in Patients with Psoriasis Vulgaris and Normalizes Skin Pathology via Concurrent Regulation of IL-17 and IL-10

Abstract: Targeted inhibition of Rho-associated kinase (ROCK)2 downregulates the proinflammatory T cell response while increasing the regulatory arm of the immune response in animals models of autoimmunity and Th17-skewing human cell culture in vitro. In this study, we report that oral administration of a selective ROCK2 inhibitor, KD025, reduces psoriasis area and severity index scores by 50% from baseline in 46% of patients with psoriasis vulgaris, and it decreases epidermal thickness as well as T cell infiltration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 23 publications
(37 reference statements)
2
65
0
Order By: Relevance
“…KD025, published in 2008, is the first highly selective ROCK2-isoform inhibitor. 17,[63][64][65][66] In addition to the pro-beige adipogenic action of KD025, we have noticed an anti-adipogenic action of KD025 as reflected by reduced perilipin levels in the drug-treated SV cells ( Figure 7D, 7). Indeed, its therapeutic potential has been explored in fibrotic disease, 15 focal cerebral ischemia, 16,61,62 and auto-immune disease.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…KD025, published in 2008, is the first highly selective ROCK2-isoform inhibitor. 17,[63][64][65][66] In addition to the pro-beige adipogenic action of KD025, we have noticed an anti-adipogenic action of KD025 as reflected by reduced perilipin levels in the drug-treated SV cells ( Figure 7D, 7). Indeed, its therapeutic potential has been explored in fibrotic disease, 15 focal cerebral ischemia, 16,61,62 and auto-immune disease.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, its therapeutic potential has been explored in fibrotic disease, 15 focal cerebral ischemia, 16,61,62 and auto-immune disease. 17,[63][64][65][66] In addition to the pro-beige adipogenic action of KD025, we have noticed an anti-adipogenic action of KD025 as reflected by reduced perilipin levels in the drug-treated SV cells ( Figure 7D, 7). Importantly, both dose-and time-dependent analyses ( Figure 7E; Figure S8A) helped to dissociate the pro-beige adipogenic (mediated by ROCK2 inhibition) and anti-adipogenic (targets are not clear) actions of KD025.…”
Section: Discussionmentioning
confidence: 89%
“…The effect of KD025 to suppress IL‐17 and IL‐21 production was then confirmed in PBMCs from patients with rheumatoid arthritis, graft‐versus‐host disease, systemic lupus erythematosus and inflammatory bowel diseases . Further, recent Phase 2 studies showed that oral administration of KD025 reduces clinical scores in psoriasis patients with concomitant decrease in plasma levels of IL‐17 and IL‐23 and increase in that of IL‐10 .…”
Section: Rho Signaling Research In Current Statusmentioning
confidence: 87%
“…To detect palmitoylation, RPE1 cells transfected 48 hours earlier with different Myc-tagged constructs were starved for 1 hour at 37 °C in IM (Glasgow minimal essential medium buffered with 10 mM Hepes, pH 7.4), incubated for 2 hours at 37 °C in IM with 200 µCi/ml 3 H palmitic acid (9, For GDI1 co-immunoprecipitation assay, HEK cells were lysed using 50 mM TRIS base, Triton 2 %, 200 mM NaCl as well as 1 tablet/10 ml protease inhibitor Mini-complete, EDTAfree (Roche). After removal of insoluble fragments via centrifugation at 12,000 g for 25 min, lysates were incubated with 15 µl of GFP-Trap Agarose beads from Chromotek for 1 h at 4 °C on a rotary wheel.…”
Section: Biochemistrymentioning
confidence: 99%
“…Previous findings classify psoriasiform manifestations in the group of AID. In such cases, elevated levels of active RhoA and Rac1 have been reported 9,10 . Recently, Gernez et al reported 4 patients with severe autoinflammation that were successfully treated with IL-1 inhibition and identified 3 distinct de novo heterozygous variants in the C-terminal part of the Cdc42 11 .…”
Section: Introductionmentioning
confidence: 99%